CONTENT AGGREGATOR: PROBLEM ETIS JURNALISME ONLINE DI INDONESIA - Prilani, Prilani (Universitas Merdeka Malang, 2017)
AbstractThe rapid development of information and communication technology has led to the problem of journalism in Indonesia. Existing codes of ethics and rules seem to be just a scientific ornament in the practice of journalism. The appreciation for journalistic work is fading when there is a portal/web collecting other news to be aired again. Content aggregator as news gathering becomes a serious phenomenon for the continuity of journalism production. Collecting news and producing journalistic writings without media permission has been considered a custom. Yet ethically they are faced with the fact that producing credible news cant be done easily. Ethical issues in the context of Content Aggregator are divided into two sections; Presentation of news and news gathering, so it is necessary to approach ethical level for media industry as perpetrator, that is; Meta-ethics, Normative Ethics and Applied Ethics that organize media practitioners to apply journalism properly. This ethical problem can actually be anticipated through strict regulation of the opening of web/portal collecting news in vain. The logical consequence of information technology changes containing news from others is feared to undermine the grip of journalism so that the creation and enactment of media convergence legislation is a must. Keywords: Content Aggregator, Ethical Problems, Online JournalismDOI :Â https://doi.org/10.26905/nomosleca.v3i1.1483